The leisure industries - Roberts, Ken (Palgrave Macmillan, 2004)
The Leisure Industries is the first book to scan the entire field of leisure from the point of view of leisure providers rather than from a demand-side perspective. Arguing that each type of supplier (commercial, voluntary and public) has special capacities, the text explores the distinctive character and qualities of the main types of leisure, from the "big three" of tourism, the media and hospitality, to activities such as shopping, sport, gambling and "events." Case studies, quotes, empirical data and boxed discussion of key theories all help to structure this text and give it a reader-friendly feel.